Optimization of the center of mass trajectory in slalom skiing - a single-track pilot approach - Flores, F. G.; Wimmer, M. A.; Kecskeméthy, A. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Curve fitting using smooth piecewise polynomial curves (Splines) allows to optimize complex spatial trajectories with the help of non-linear optimization routines. In this pilot study, a slalom skier was modeled as a point mass following a given single track in a slalom course. The study sought to identify the optimal lateral sway of the center of mass as well as up and down movements to minimize skidding and time